2008
DOI: 10.1111/j.1529-8817.2008.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

COOLIA CANARIENSIS SP. NOV. (DINOPHYCEAE), A NEW NONTOXIC EPIPHYTIC BENTHIC DINOFLAGELLATE FROM THE CANARY ISLANDS1

Abstract: A new photosynthetic dinoflagellate species, Coolia canariensis S. Fraga sp. nov., is described based on samples taken from tidal ponds on the rocky shore of the Canary Islands, northeast Atlantic Ocean. Its morphology was studied by LM and SEM. It is almost spherical and has a thick smooth theca with many scattered pores. Plate 1' is the biggest of the epithecal plates, and 7″ is twice as wide as it is long. Phylogeny inferred from the D1/D2 regions of the LSU nuclear rDNA of three strains of C. canariensis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 39 publications
(89 reference statements)
14
68
0
9
Order By: Relevance
“…In agreement with the results of Penna et al (2005), only slight geographical differences can be observed among the different strains from the Mediterranean and the local isolates of C. monotis, which appear to belong to a single evolutionary lineage, whereas the New Zealand strain constitutes a genetically distinct entity described as Coolia malayensis (Leaw et al, 2010). Similar relationships were inferred by Fraga et al (2008) who found three different lineages within selected strains of the genus Coolia, one of them including strains of C. canariensis, a second with C. monotis from Indonesia and Belize and a third containing two sister groups, one corresponding to C. monotis from European localities and the other to C. monotis and C. malayensis from New Zealand, Malaysia and Florida. The local strains morphologically identified as Ostreopsis cf.…”
Section: Phylogenysupporting
confidence: 75%
See 4 more Smart Citations
“…In agreement with the results of Penna et al (2005), only slight geographical differences can be observed among the different strains from the Mediterranean and the local isolates of C. monotis, which appear to belong to a single evolutionary lineage, whereas the New Zealand strain constitutes a genetically distinct entity described as Coolia malayensis (Leaw et al, 2010). Similar relationships were inferred by Fraga et al (2008) who found three different lineages within selected strains of the genus Coolia, one of them including strains of C. canariensis, a second with C. monotis from Indonesia and Belize and a third containing two sister groups, one corresponding to C. monotis from European localities and the other to C. monotis and C. malayensis from New Zealand, Malaysia and Florida. The local strains morphologically identified as Ostreopsis cf.…”
Section: Phylogenysupporting
confidence: 75%
“…The morphology of C. canariensis corresponds well with the original description of Fraga et al (2008), except for the morphology of thecal pores of plate 1 0 , which are round in our strain but described as oval in the original description, and the cell dimensions, which are slightly larger in the local strains. The tabulation pattern of C. canariensis is very similar to that of C. areolata, but thecal ornamentation allows differentiation of the two species.…”
Section: Taxonomic Remarkssupporting
confidence: 51%
See 3 more Smart Citations